Characterization of a novel mouse model of multiple myeloma and its use in preclinical therapeutic assessment. - Rosemary A Fryer; Timothy J Graham; Emma M Smith; Simon Walker-Samuel; Gareth J Morgan; Simon P Robinson; Faith E Davies (PLoS ONE)
To aid preclinical development of novel therapeutics for myeloma, an in vivo model which recapitulates the human condition is required. An important feature of such a model is the interaction of myeloma cells with the bone marrow microenvironment, as this interaction modulates tumour activity and protects against drug-induced apoptosis. Therefore NOD/SCIDγc(null) mice were injected intra-tibially with luciferase-tagged myeloma cells. Disease progression was monitored by weekly bioluminescent imaging (BLI) and measurement of paraprotein levels. Results were compared with magnetic resonance imaging (MRI) and histology. Assessment of model suitability for preclinical drug testing was investigated using bortezomib, melphalan and two novel agents. Cells engrafted at week 3, with a significant increase in BLI radiance occurring between weeks 5 and 7. This was accompanied by an increase in paraprotein secretion, MRI-derived tumour volume and CD138 positive cells within the bone marrow. Treatment with known anti-myeloma agents or novel agents significantly attenuated the increase in all disease markers. In addition, intra-tibial implantation of primary patient plasma cells resulted in development of myeloma within bone marrow. In conclusion, using both myeloma cell lines and primary patient cells, we have developed a model which recapitulates human myeloma by ensuring the key interaction of tumour cells with the microenvironment.